Is there discrimination against children of same-sex households? Evidence from an experimental study in Colombia - Natalia Cantet; Brian Feld; Mónica Hernández (Inter-American Development Bank (IDB), 2023)
We measure the extent of discrimination against same-sex couples by schools in Colombia using a matched-pair correspondence study. We send requests to visit private schools from several couples of different sexual orientation as conveyed by the names of the parents. We track the response rate from schools, the time to reply and the quality of the reply. We find that schools are 12 percentage points (22.3%) less likely to respond to a request sent by a homosexual couple with respect to one sent by a heterosexual one. When no information about sexual orientation is provided, the response rate decreases by 20pp. (37%) versus an explicitly heterosexual couple. Conditional on replying, we find no difference in the time schools take to respond or the quality of the reply across couples, a result plausibly driven by selection into responding. Our findings suggest that, despite a strong legal framework that protects LGBTQ+ rights, discrimination against same-sex couples is pervasive and can have intergenerational consequences.
Keywords: I24; J15; J16; 330; School discrimination; Same-sex parents; Correspondence study